Constitution 3.0 freedom and technological change - Rosen, Jeffrey 1964-; Wittes, Benjamin (Brookings Institution Press, 2011)
"Explores the challenges to constitutional values posed by sweeping technological changes such as social networks, brain scans, and genetic selection and suggests ways of preserving rights, including privacy, free speech, and dignity in the age of Facebook and Google"--Provided by publisher.